Transcripts of "Nigeria, Hausa program series, 1968-1970" - La Guma, Alex; Duerden, Dennis ([Dennis Duerden collection of sound recordings relating to African novelists, poets, playwrights, artists and musicians; African history, politics, and social questions], 2012)
This Hausa collection contains 5 plays by Alex La Guma, oral traditions, and discussions on the following topics: journalism, change and control, African leaders, human rights, cities, need for law, contact and conflict, travellers in Africa, migration, Africa and the world and His Excellency the Ambassador.